Impact of Second-Parent Migration on Student Academic Performance in Northwest China and its Implications. Issue 8 (2nd August 2020) - Bai, Yu; Neubauer, Michael; Ru, Tong; Shi, Yaojiang; Kenny, Kaleigh; Rozelle, Scott
Abstract: The migration of hundreds of millions of rural Chinese workers to the city has contributed substantially to China's economic growth since the beginning of the country's economic reform in 1978. However, this migration has also led to societal issues, including more than 60 million left-behind children. Empirical studies that seek to measure the impact of being left-behind on academic performance have led to inconsistent results, perhaps because the effects may be different for first-parent migration (migration during the first period of time in which one parent migrates) and second-parent migration (migration when the remaining parent leaves the home). Here we have examined how school performance changes before and after the second parent out-migrates. We use a panel dataset of over 5, 000 students from 72 primary schools in rural China. Using a difference-in-difference approach, supported by a placebo test, we find that second-parent migration has statistically significant negative impacts on student performance. Importantly, our data provide convincing evidence that second-parent migration has a more negative impact on academic performance than first-parent migration. Our results have broad implications for China's future economic growth and inequality.